Kharadar spontaneous quintuplets reached their adolescence life. A case report - Ahmed, Mubashir; Iqbal, Khalid; Birdie, Havovi; Rizvi, Syed Shakil Ahmed; Haq, Rabia; Waseem, Shumaila (Journal of the Pakistan Medical Association, 2024)
Quintuplet pregnancies are associated with significant perinatal morbidity and mortality. The spontaneous quintuplets are a rare occurrence, and the survival is extremely rare. The first quintuplets known to survive infancy to adulthood were the Dionne Quintuplets, born in 1934. Kharadar quintuplets born in 2006, in Karachi Pakistan, were the first set of quintuplets who were born alive and reached their adolescence. A 30-year old women, presented at Kharadar General Hospital (KGH) during the 28th week of gestation for pregnancy evaluation. She was diagnosed with a quintuplet pregnancy with no gross foetal abnormality on ultrasound abdomen. The patient had premature rupture of membrane at 30th week of gestation, and emergency caesarean section was performed. All five quints were born alive, had normal APGAR scores, were premature, and had low birth weight. After birth, all quints were immediately shifted to the neonatal intensive care unit. ---Continue